PERSEPSI TAHUN PEMBINAAN WAJIB PAJAK MEMODERASI KUALITAS LAYANAN DAN NIAT TERHADAP KEPATUHAN WAJIB PAJAK (Studi Empiris Pada KPP Pratama Semarang Timur) - Ella Rahmawati, 14.05.52.0299; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2017)
This research aims to analyze the quality of services, intentions, and the TPWP program on tax compliance in KPP Pratama East Semarang. The population in this study are corporate taxpayers listed in KPP Pratama East Semarang. This research uses primary data. Sampling was done by using the convinience sampling method and obtained as many as 100 respondents. Techniques of analysis using multiple regression models with moderating absolute difference on based. The results showed that the quality of service has no effect on tax compliance. Intention effect on tax compliance.TPWP no effect on tax compliance. TPWP not moderate the relationship of service quality and intentions on tax compliance, which means TPWP not found moderating so it has no effect on tax compliance.Keywords:Â Tax Compliance, Quality Of Service, Intentions, and TPWP